Leader Humility and Knowledge Sharing Intention: A Serial Mediation Model - Nguyen, Diep T. N.; Teo, Stephen T. T.; Halvorsen, Beni; Staples, Warren (Frontiers in Psychology, 2020)
This paper examines the influence of leader humility on knowledge sharing intention. Drawing on social exchange theory (SET), we examine the direct and indirect mechanisms to explain the influence leader humility has on knowledge sharing intentions. A two-wave, time-lagged field study was conducted where we surveyed 252 professional employees from Australia. The proposed model was analyzed using structural equations modelling. Results show a significant direct, positive association between leader humility and employees’ knowledge sharing intention. While leader humility had a direct, positive associations with affective trust in supervisor and work engagement, it did not directly impact on organizational citizenship behavior directed toward the individual (OCB-I). There was three SET-related, serial mediation mechanism of the impact of leader humility on knowledge sharing intention. These were affective trust, work engagement, and OCB-I. Theoretical and managerial implications will be discussed in relation to the development of knowledge sharing intentions via the social exchange mechanisms of humility leadership.